Principles of Environmental Policy in the Law of the European Union - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The wide range of directives and regulations of the European Union on the protection of environment is based on several principles, traditionally divided into two groups: the principles of environmental policy and the principles of implementation of measures aiming to protect the environment. The former are the principles of sustainable development and high protection of the environment, while the latter the principle of subsidiarity and proportionality, principle of environmental integration, precautionary principle, principle of prevention, the principle of rectification of environmental damage at its source and the “polluter pays” principle.In this paper the subject of analysis are only the principles of environmental policy. The content of the notion of sustainable development is not outlined in the primary and secondary sources of EU law, but in political acts of international and community origin. It is defined as development that meets the needs of present generations without compromising the ability of future generations to meet their own needs. The basic problem in the interpretation of this concept is to indentify standards based on which given activities may be considered as development compromising the ability of future generations to meet their needs and to project such potential needs.The principle of high level of protection of the environment is not easier to interpret either. The elements of its content that seems to be undisputed and generally recognized is that it should not to be interpreted as the highest possible level of protection, on the one hand, and that it should be determined according to standards adopted by countries that have more developed environmental protection, preferably, but not necessarily members of the European Union, on the other. The greatest insufficiency of both principles, which virtually compromises their legal nature and hence hinders implementation of direct legal sanctions, is that they, besides ecological, comprise economic and social considerations as well.The author approves the standpoint adopted in literature that by elimination of economic and social considerations from notions of sustainable development and high level protection of the environment, or at least by a decrease in their importance, and a strengthening of ecological considerations, these principle might become legal rules with direct legal sanctions, i.e. the Court of Justice might annul directives and regulations not in compliance with them.